1994
DOI: 10.1046/j.1537-2995.1994.34694295059.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of blood transfusion

Abstract: Incidence rates of blood transfusion for "causal" planning of blood collections are presented here for the first time. The probability of receiving a transfusion of RBCs in any year rises by 20-fold from the rate in those less than 40 years old to that in those more than 65 years old, who receive 53.3 percent of the red cell units transfused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
8

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 14 publications
7
127
0
8
Order By: Relevance
“…some previous studies. 15 Abortion (4%) was more than expected in our study as a cause of blood utilization which may be backstreet abortion or due to social and cultural factors in that area. More study is needed to nd out the reason behind it.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…some previous studies. 15 Abortion (4%) was more than expected in our study as a cause of blood utilization which may be backstreet abortion or due to social and cultural factors in that area. More study is needed to nd out the reason behind it.…”
Section: Discussionmentioning
confidence: 45%
“…Previous studies also showed a prevalence of female patients in indication of blood transfusion. 15 In other countries, the male-female ratio was shown as 43:57 17 , 48:52 18 , 45:55 15 , and as 51:49. 9 On this basis, in our study, it was 29:71 where ratio of the female patients was signi cantly higher in spite of having same pattern of indications like those studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of autologous blood transfusion grew in the early 1990s but has since decreased; autologous transfusion constituted only 3.7 percent of the units administered in 1997 (31). Using data obtained from a rural, suburban US county, the annual probability of receiving a red blood cell transfusion has been estimated at approximately 9 per 1,000 persons, but this probability increases to 50 per 1,000 among persons older than 65 years (32). Surveys of transfusion practices over the past 20 years have shown cancer to be among the leading indications for transfusion, ranging from 10 percent to 30 percent of all units and patients-a level similar to that for cardiovascular and gastrointestinal disease (33)(34)(35)(36).…”
Section: Blood Transfusion As a Risk Factormentioning
confidence: 99%
“…Due to the increased number of surgical interventions and their progressive complexity, particularly in higher-developed countries [1,4,12,13,14,15,16], the demand for blood products has increased globally, as noted by a demographic analysis [17]. Additionally, older patients require more blood transfusions [14,18,19] as a result of progress in medical sciences and therapeutic options [17]. Additionally, the demographic ageing of the population in higher developed countries may even reduce the number of younger individuals without illness who have preferentially been recruited as voluntary blood donors [4,12,14,15,20,21].…”
Section: Introductionmentioning
confidence: 99%